Constructing Home Safety Indices for Strategic Planning in Residential Real Estate - Oliveira, I.; Carayannis, E.; Ferreira, F.; Jalali, M.; Carlucci, D.; Ferreira, J. (2017 BAI International Conference, 2017)
Residential safety and perceptions thereof directly influence the daily habits of an area’s residents, as well as its levels of economic activity, and the revenue generated and traded in its real estate. These variables, in turn, impact the flows of local population, and ultimately the socio-economic development of the region. Although residential safety, and its determinants in particular, have been widely studied, many of the existing contributions recorded are seen as restrictive in terms of the manner in which the evaluation criteria are identified, and the relationships between them analyzed. The current study aims to address these issues, through the integrated application of cognitive mapping techniques with the Analytic Hierarchy Process (AHP) method. Based on group sessions involving a panel of urban planners and residential safety experts, and taking on a constructivist approach, a residential safety evaluation system was created, tested and validated, revealing promising results in the identification of the safest residential areas. The advantages and limitations of the methodological proposal presented are also discussed.